PROMOTING WRITING EXPERIENCES THROUGH LEARNING COMMUNITY TO TRIGGER STUDENTS IN WRITING - Yamin, Muhammad (Department of English Language Education, UIN Sunan Ampel Surabaya, 2018)
This study aims at discussing the importance of promoting writing experiences through learning community to trigger students in writing. This is review study with analytic descriptive way by describing and discussing the related literature studies. It deals with writing experiences as the capital to write. While there is no experience, there is no writing. Learning community used in this study is the learning facility so that the students can learn how to write. More active in learning community, the student get the knowledge and experience of writing. Those become the inspiration for them to rewrite what to write.